Parent-of-origin effects on nuclear chromatin organization and behavior in a Drosophila model for Williams–Beuren Syndrome - A. V. Medvedeva; E. V. Tokmatcheva; A. N. Kaminskaya; S. A. Vasileva; E. A. Nikitina; A. V. Zhuravlev; G. A. Zakharov; O. G. Zatsepina; E. V. Savvateeva-Popova (Вавиловский журнал генетики и селекции)
Prognosis of neuropsychiatric disorders in progeny requires consideration of individual (1) parent-of-origin effects (POEs) relying on (2) the nerve cell nuclear 3D chromatin architecture and (3) impact of parent-specific miRNAs. Additionally, the shaping of cognitive phenotypes in parents depends on both learning acquisition and forgetting, or memory erasure. These processes are independent and controlled by different signal cascades: the first is cAMPdependent, the second relies on actin remodeling by small GTPase Rac1 – LIMK1 (LIM-kinase 1). Simple experimental model systems such as Drosophila help probe the causes and consequences leading to human neurocognitive pathologies. Recently, we have developed a Drosophila model for Williams–Beuren Syndrome (WBS): a mutant agnts3 of the agnostic locus (X:11AB) harboring the dlimk1 gene. The agnts3 mutation drastically increases the frequency of ectopic contacts (FEC) in specific regions of intercalary heterochromatin, suppresses learning/memory and affects locomotion. As is shown in this study, the polytene X chromosome bands in reciprocal hybrids between agnts3 and the wild type strain Berlin are heterogeneous in modes of FEC regulation depending either on maternal or paternal gene origin. Bioinformatic analysis reveals that FEC between X:11AB and the other X chromosome bands correlates with the occurrence of short (~30 bp) identical DNA fragments partly homologous to Drosophila 372-bp satellite DNA repeat. Although learning acquisition in a conditioned courtship suppression paradigm is similar in hybrids, the middle-term memory formation shows patroclinic inheritance. Seemingly, this depends on changes in miR-974 expression. Several parameters of locomotion demonstrate heterosis. Our data indicate that the agnts3 locus is capable of trans-regulating gene activity via POEs on the chromatin nuclear organization, thereby affecting behavior.